Home point-of-care international normalised ratio monitoring sustained by a non-selective educational program in children - Bajolle, Fanny; Lasne, Dominique; Elie, Caroline; Cheurfi, Radhia; Grazioli, Aurélie; Traore, Maladon; Souillard, Patrick; Boudjemline, Younes; Jourdain, Patrick; Bonnet, Damien (Thrombosis and Haemostasis, 2012)
Adverse events related to vitamin K antagonist (VKA) therapy might be reduced by point-of-care international normalised ratio (POC INR) monitoring supported by an education program (EP). Our aim was to evaluate the efficacy of a non-selective VKA paediatric EP (regardless of the social, economic, educational or linguistic levels) by analysing the time spent in the therapeutic range (TTR), VKA adverse events and compliance to treatment, and INR control prescriptions. The EP was modified from the pediatric EP previously described but improved by a specifically devised child-focused game. One hundred four consecutive children (median age 8 years) receiving VKA were included in a standardised E P. Patients were in self-testing, and dose adjustments were made by a single physician for three tolerance ranges according to the underlying disease: [2.5–4], [1.8–3.2], and [1.5–2.5]. The median follow-up was 481 days [70–1,001]. The overall TTR was 81.4% [36–100]. The TTR were 74%, 85.6% and 89% for the ranges [2.5–4], [1.8–3.2], and [1.5–2.5], respectively. These results were sustainable during the study period. Only one serious VKA adverse event was recorded. The median number of POC INR tests was 2.5 [1.6–5.7] INR per patient and month. Patients/families performed POC INR when requested in 86.9% of the cases. More than 90% of the families found the EP supportive and wished to follow a long-term reinforcement program. In conclusion, this non-selective child-focused EP for VKA therapy, strongly supported by our dedicated game, is useful in maintaining efficacy, safety and compliance to anticoagulation and its monitoring.
Keywords: Congenital heart disease/defects; education; anticoagulation; point-of-care INR monitoring; children & adolescents